World Action In Improving The Efficiency Of Logistics Services And The Importance Of Its Development In Our Country (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this article, logistics services provide high efficiency of the logistics services and the national cylinder of the cylinder is the cylinder of the cylinder, adapting the country's cylinder to world standards, ensuring national logistics infrastructure and, thanks to it, free turnover, Practical recommendations are made to deepen cooperation and improve the competitiveness of products not only in our country but also in the world.